Study on Desorption Experiment and Desorption Model of Deep Shale Gas Containing Water - Zuping Xiang; Yangyang Ding; Xiang Ao; Zehua Cheng; Qianhua Xiao; Zhezhi Liu; Shijie Zhu; Zhonghua Chen (Advances in Materials Science and Engineering)
In this work, the methane desorption isothermal curves at different water contents on deep sampled from Western Chongqing of China were measured at pressures up to 65 MPa and at 130°C by the volumetric method. In the first instance, the desorption increases with the decrease of pressure, the adsorbed gas desorbs slightly with decreasing pressures from 65 to 30 MPa. When the pressure drops to 30–20 MPa, the desorption rate increases rapidly with the decrease of pressure and the desorption curve begins to separate from the adsorption curve, resulting in desorption hysteresis. At last, when the pressure is lower than 20 MPa, the desorption increases almost linearly with the further decrease of pressure, but eventually there will be some adsorbed gas which cannot be desorbed to form residual adsorbed gas. After that, the isotherm desorption data of CH4 was fitted using the improved desorption model. The fitting results showed that the improved desorption model can be used to describe the desorption process of deep shale gas containing water and has a strong applicability. In addition, the critical desorption pressure increases with increasing water content. When the water content is lower than 1%, the effect of the water content on the desorption of deep shale gas increases rapidly with increasing water content, as well as when the water content is greater than 1%, the impact changes slowly.